Analisis Target Costing dalam Optimalisasi Laba Usaha Mikro Kecil Menengah - Rakhmawati, Ita; Mui'jz, Muhammad Abdul (JIOSE: Journal of Indonesian Sharia Economics, 2023)
Profit is one indicator to maintain the sustainability of the company. In order to achieve optimal profit, the company must charge the product appropriately. The purpose of this research is to apply the target costing method in order to make production costs efficient at the Iqbal Collection. This research is a qualitative research with a case study design. Data sources include primary data and secondary data. Primary data obtained through interviews and observation. Secondary data obtained through documentation. The results showed that the production costs incurred by the company before implementing target costing were Rp. 52,905,000.00. Whereas after the implementation of target costing, the costs incurred by the company amounted to Rp. 49,905,000.00. This indicates a cost efficiency of 5.67% in the application of target costing. Viewed from the aspect of profit acquisition, the profit obtained before the implementation of target costing was Rp. 2,595,000.00. Meanwhile, after the implementation of target costing, the profit obtained was Rp. 5,595,000.00. Conditions indicate that target costing is proven capable of optimizing profits at a level of 10.08%.